A case report on the 2017 highly pathogenic avian influenza (H5N1) outbreak in poultry in Kelantan - Zubaidah, M. A. (2020)
Highly pathogenic avian influenza (HPAI) is caused by influenza virus A from the family Orthomyxoviridae. It is a severe, systemic disease with high mortality in avians. The mortality can be as high as 100% in a few days. On 28 February 2017, HPAI virus of H5N1 subtype was confirmed in village chickens at Kampung Pulau Tebu, Batu 5, Tunjong Kota Bharu, Kelantan. It was the second outbreak of HPAI in Kelantan after the first reported case at Tumpat Kelantan on 17 August 2004. Most of the dead poultry showed similar clinical signs of sudden death with high mortality, cyanosis and oedema of head, comb, wattle and snood as well as red discolouration of shanks and feet. Post-mortem was performed on dead poultry and there were generalised haemorrhages of all internal organs, congested mesenteric blood vessels and pinpoint haemorrhages on proventriculus. Histopathological examination revealed generalised pulmonary haemorrhages with moderate interstitial pneumonia, generalised hepatic haemorrhages and hepatitis with multifocal area of hepatic necrosis, generalised haemorrhagic myocarditis and generalised haemorrhagic nephritis. Confirmation test was performed using RT-PCR and viral isolation at Veterinary Research Institute, Ipoh. 36 foci were affected involving five districts (Kota Bharu, Tumpat, Bachok, Pasir Mas and Tanah Merah) causing depopulation of 56,953 poultry and 17,531 eggs. Surveillance and control measures were taken by Department of Veterinary Services to contain the disease from spreading to other areas.